PENGARUH TEKNIK PERNAFASAN BUTEYKO TERHADAP PENURUNAN FREKUENSI KEKAMBUHAN ASMA PADA PASIEN PENDERITA ASMA - Baroroh, Irfah (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Asthma is a disease that is very close to the community and has an ever-increasing population. The prevalence of asthma in Indonesia is 3.5 % . Prevalence of asthma in Bengkulu, especially Rejang Lebong in 2012 amount 1.606 people. Higher data in Kampung Delima Working Area Health Center are 182 peoples and theres 53 people (29,12%) feels recurrence. This study aimed to determine the effect of buteyko breathing techniques to decrease the frequency of recurrence of asthma in asthmatics in Kampung Delima Working Area Health Center. This study was pre Experimental design using one group pre and post test. Populations of this study are 182 people. The samples were taken with accidental sampling technique which amounts to 30 people. The distribution of the average frequency of recurrence of asthma before being given Buteyko breathing technique is 3.40 and the average frequency after the Buteyko breathing technique given is 2.07 . Based on the analysis of test data is obtained , which means there is the influence of the Buteyko breathing technique to decrease the frequency of recurrence of asthma in the Work Area Kampung Delima health center (p=0,000).